Brief Analysis of the Characters of Mulan in Mulan Poem - Deng, Jie (International Journal of Social Sciences and Public Administration, 2024)
As an ancient female character who volunteered to serve in the army on behalf of her father, Hua Mulan became a hero in ancient Chinese literature due to her perseverance, bravery and loyalty. At the same time, she expressed the noble character of strong courage and the spirit of sticking to the family responsibility also highlights the important position of women in ancient society. The purpose of this paper is to make an in-depth analysis of the image of Mulan, the main character in the ancient Chinese literary work Mulan Poem, which is of great significance for understanding the image of female roles in ancient literary works and Chinese traditional culture.